Holy Quran Counseling to Reduce Self Doubt - Burhani, Iqbal Khoirul; Permatasari, Karin Sufi; Primananda, Fradifa (Proceedings of International Conference on Da'wa and Communication, 2021)
Self-doubt stems from a person's doubts about himself with what he has seen and evaluation of the abilities of others. But he felt unable to do so. This of course must be immediately followed up with various therapies that are possible to reduce and even permanently eliminate this self-doubt in someone. Self-doubt sometimes gives rise to new branches of problems that can have a bad effect on a person. In this case, the counselor tries to provide treatment that is Islamic In nature by using the teachings of the verses of the Qur'an which can be used as medicine or therapy for the counselee. Researchers will take the content in the verses of the Qur'an which will later be used as medicine or therapy for clients who have self-doubt. The research method in this study is a literature review sourced from related books and journals